Complicaciones infecciosas en cirugía digital - Alou Cervera, Luis; Maestre Vera, Juan Ramón; Sevillano Fernández, David; Prieto Prieto, José (Revista Internacional de Ciencias Podológicas, 2007)
The authors expose the infectious complications after the accomplishment of surgical techniques in the foot as well as the antimicrobial treatment of election.